Ionospheric Plasma Density Oscillation Related to EMIC Pc1 Waves. Issue 15 (3rd August 2020) - Kim, Hyangpyo; Shiokawa, Kazuo; Park, Jaeheung; Miyoshi, Yoshizumi; Miyashita, Yukinaga; Stolle, Claudia; Kim, Khan‐Hyuk; Matzka, Jürgen; Buchert, Stephan; Fromm, Tanja; Hwang, Junga
Abstract: We report the first observation of plasma density oscillations coherent with magnetic Pc1 waves. Swarm satellites observed compressional Pc1 wave activity in the 0.5–3 Hz band, which was coherent with in situ plasma density oscillations. Around the Pc1 event location, the Antarctic Neumayer Station III (L ~ 4.2) recorded similar Pc1 events in the horizontal component while NOAA‐15 observed isolated proton precipitations at energies above 30 keV. All these observations support that the compressional Pc1 waves at Swarm are oscillations converted from electromagnetic ion cyclotron (EMIC) waves coming from the magnetosphere. The magnetic field and plasma density oscillate in‐phase. We compared the amplitudes of density and magnetic field oscillations normalized to background values and found that the density power is much larger than the magnetic field power. This difference cannot be explained by a simple magnetohydrodynamic (MHD) model, although steep horizontal/vertical gradients of background ionospheric density can partly reconcile the discrepancy. Plain Language Summary: Electromagnetic ion cyclotron (EMIC) wave is known to be generated in the inner magnetosphere in the ultralow frequency (ULF) Pc1 range (0.2–5 Hz). The EMIC Pc1 waves propagate as shear Alfvén mode from the magnetospheric source toward the ionosphere. On arriving at ionospheric altitudes, they undergo mode conversion to the compressional Alfvén mode due to the Hall conductivity. According to the ideal magnetohydrodynamics (MHD) theory, the compressional ULF wave can be accompanied by density perturbation of ionospheric plasmas. In this paper, we report the first observation of ionospheric plasma density oscillations driven by EMIC Pc1 waves based on the observation by the Swarm satellites. Simple MHD equations cannot fully explain the amplitude and phase relationship between plasma density and magnetic Pc1 pulsations, while steep horizontal/vertical gradients of background ionospheric plasma density may in part reconcile the discrepancy. Key Points: We report the first observation of ionospheric plasma density oscillation correlated with electromagnetic ion cyclotron (EMIC) Pc1 wave Simple MHD theory cannot explain the observed amplitude and phase relationships between the plasma density oscillation and the Pc1 wave The EMIC Pc1 wave was also accompanied by localized proton precipitation